Impact of agricultural abandonment on soil organic carbon: The case of semi‐steppe rangeland in Central Iran. (4th July 2022) - Pajouhesh, Mehdi; Salari, Samira; Tahmasebi, Pejman; Nikookhah, Farzane; Azadi, Hossein; Sklenička, Petr; Witlox, Frank
Abstract: This study investigated the change in soil organic carbon (SOC), soil labile carbon (C), soil total nitrogen (N), particulate organic carbon (POC), mineralizable soil C (Min‐C) in soil aggregate fractions, and soil particles size at 0–30 cm soil depth of the semi‐steppe rangelands in Central Iran (Sheida and Khargosh regions). The study used a fully randomized design with four land uses in the rangelands including covered with rainfed wheat (CR0), abandoned rangelands (ARs) for 5–15 years (AR15), abandoned rangeland for 16–40 years (AR40), and permanently uncultivated rangelands (UR) as the reference sites that were replicated three times ( n  = 3) with at most 2 km distance from each other in an area of 25 ha. For each treatment, the soil samples were randomly obtained at 0–30 cm soil depth in three replicated plots of 2 × 2 m using a core size of 7 cm in diameter. The samples were mixed to take a composite soil sample (12 soil samples in each region) in June 2018. The results indicated that soil POC is the most sensitive fraction for the identification of shifts in the total SOC after the cultivation cessation because by increasing the abandoned land and the cessation of cropland activities, the POC has also increased. In conclusion, after the cessation of rainfed cropping and the recovery of natural vegetation, the increases in soil microorganism activity can result in a higher nutrient cycling in the degraded rangeland ecosystems.